Perancangan File Cloud Host Berbasis Nexcloud - Wati, Nursetia (Jurnal Teknologi Informasi Indonesia (JTII), 2023)
The purpose of this study is to maximize archive management at SMK 1 Limboto School by implementing a Private Cloud Storage System using the Nextcloud storage application. The background to taking the title above is because there is no centralized storage of documents in the form of softcopy, complicated coordination and a long time to fulfill requests for evidence and there is no system that can store and can be accessed. The system that will be built by utilizing cloud storage technology provides convenience to large file storage capacity and access in real time (anytime and anywhere). The cloud technology used is Nextcloud which is client-server software for creating and using file hosting services. It is functionally similar to Dropbox or Google Drive in that it allows anyone to store and share data. The results of utilizing the Cloud Storage system are very relevant to current conditions where data requests and data access can be done without conducting face-to-face meetings. For the performance of employees and teachers with all human resource limitations can improve archive management and fast data access services.